Factors involved in the biogeography of the honey locust tree (Gleditsia triacanthos) invasion at regional scale: an integrative approach. - Romero-Pacheco, David; Sosa, Beatriz; Brazeiro, Alejandro; Achkar, Marcel; Guerrero, José Carlos (Springer Nature, 2021)
Native to the southeastern United States, the honey locust (Gleditsia triacanthos) is an invasive tree in several South American countries. Since eradication of invasive species is often costly, prevention is a better strategy. The relationship between invasive species and their habitats can be analyzed using species distribution models to produce maps of areas prone to the invasions. These maps can be used to develop efficient early detection plans of exotic species colonization. Here, we employed the Favorability Function model to assess the effects of environment and human activities on the invasive process of the honey locust in Uruguay. By integrating environmental and anthropic factors in our models, we obtained the best fitted prediction and classification indices. We showed that the southwestern region of the country concentrates the largest proportion of areas prone to the invasions. Environment was the main factor explaining the invasion of G. triacanthos, but the effect of human-related factors had a greatest effect in combination with environmental variables than on its own. We generated favorable risk maps and explanatory variables that can be used to more efficiently plan efforts to control the spread of this invasive.
https://openpolicyfinder.jisc.ac.uk/id/publication/16215
Keywords: Acacias; Especies exóticas invasoras - Control; Disturbed territories; Environmental characteristics; Invasion risk map; Favorability Function; Anthropic influences; Spread prevention